Sudden infant deaths in sitting devices. Issue 5 (19th July 2007) - Côté, A; Bairam, A; Deschenes, M; Hatzakis, G
Abstract : Background: As episodes of decreased oxygenation levels have been recorded in premature infants placed in car seats, it is believed that these infants are at risk of life-threatening events and death. No data on the prevalence of such infant deaths are available. The aim of our study was to determine the incidence of sudden deaths in infants occurring in sitting devices in a whole population and to determine whether premature infants account for a disproportionate number of these deaths. Design: Retrospective population-based cohort study reviewing all cases of sudden unexpected death in infants between birth and 1 year of age that occurred in the province of Quebec between January 1991 and December 2000. Results: Of the 508 deaths reviewed, 409 were unexplained and 99 were explained after investigation. Seventeen deaths occurred in a sitting device, of which 10 were unexplained. There was no excess of premature infants dying. However, there was an excess of infants of less than 1 month of age found to have died in a sitting position in the unexplained death group. In addition, three infants who died in a sitting position had an increased risk of upper airway obstruction. Conclusion: Although very few deaths occurred in car seats, our results suggest that caution should be used when placing younger infants in car seats and similar sitting devices, whether the infants have been born prematurely or not. We also recommend that more attention be given to infants at increased risk of upper airway obstruction.